Edukasi pada Ibu Tentang Persiapan Menghadapi Perubahan Masa Menopause - Lusiatun Lusiatun; Anna Waris Nainggolan; Imarina Tarigan; Edy marjuang Purba (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Menopause is the phase where menstruation stops for a woman. Menopause is caused by the loss of function of the ovarian follicles and a decrease in estrogen levels in the blood circulation. The menopausal transition period can occur gradually, usually starting with changes in the menstrual cycle. This transition period is called perimenopause. Perimenopause can last several years and can affect physical, emotional, mental and social well-being. So physical and mental preparation is needed to face this transition period. The aim of this community service is to provide education about menopause and prepare mothers as early as possible to face the menopause period. This activity was carried out in Sungai Jernih Hamlet, RT 10, Bajubang District, Batanghari Regency. Educational activities are carried out using lecture and discussion methods using leaflet media. The results of this activity showed that there was an increase in the level of maternal knowledge in the good category in the pre-test from 4 respondents (21%) to 16 respondents (84.2%) in the post-test results. So it can be concluded that there is an increase in knowledge among mothers before and after being given education about preparations for facing menopause.